Urban renewal and Historic Center of Lima: Thoughts about thecnical aspects of the morphologic reconfiguring of the 6007 and 6016 blocks of Barrios Altos - Álvarez Reátegui, Antonio (2016)
The Historic Center of Lima is the foundational and current central area of Lima’s urban social fabric; it covers an area of 239.69 ha. of which Barrios Altos represents 63 Ha. (26%). Even though it harbors patrimonial estate, very important for the city’s urban history, today it presents a high degree of social deterioration, urban blight and sensitive areas, which have a risk of collapse that could affect about 4500 families.The research focuses on two representative blocks of Barrios Altos (Cadastral codes 6007 and 6016). We start from their historical recognition, their critical situation expressed in quantitative data, the review of regulations for urban renewal and the casuistry of successful cases in Latin American cities. It allows us to reflect on the Basic Guidelines (BG) proposed by the Metropolitan Municipality of Lima for the morphological reconfiguration of both blocks; this forms part of urban renewal in Barrios Altos in search of a living, dynamic space and better living conditions.